2019
DOI: 10.1186/s12910-019-0356-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and intentions toward medical assistance in dying among Canadian medical students

Abstract: Background Medical assistance in dying (MAID) was legalized in Canada in 2016. As of July 2017, approximately 2149 patients have accessed MAID. There remains no national-level data on the perspectives of future physicians about MAID or its changing legal status. We provide evidence from a national survey of Canadian medical students about their opinions, intentions, and concerns about MAID. Methods From October 2016 to July 2017, we distributed an anonymous online surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 21 publications
5
17
0
Order By: Relevance
“…Having additional years in clinical practice is likely to play a role in residents’ willingness to participate in MAID. Our study suggests that residents are more agreeable to participate in PHD than physicians in Canada (40.9% vs. 29%) [3] but less agreeable than Canadian medical students (71%) [22]. This should be interpreted with some caution, however, as each study’s phrasing of questions on MAID differed slightly and this is known to influence participants’ agreeability with MAID [15].…”
Section: Discussionmentioning
confidence: 90%
“…Having additional years in clinical practice is likely to play a role in residents’ willingness to participate in MAID. Our study suggests that residents are more agreeable to participate in PHD than physicians in Canada (40.9% vs. 29%) [3] but less agreeable than Canadian medical students (71%) [22]. This should be interpreted with some caution, however, as each study’s phrasing of questions on MAID differed slightly and this is known to influence participants’ agreeability with MAID [15].…”
Section: Discussionmentioning
confidence: 90%
“…6 A recent survey of medical students showed that among Canada's new generation of doctors, 71% would offer MAiD. 7 Although provisions are in place to ensure physicians can decline to help on moral or religious grounds, researchers in Quebec found that the majority of physicians who refused to participate did not oppose MAiD. Rather, their expressed concern was "the emotional burden related to this act and the fear of psychological repercussions."…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many researchers have investigated the complex challenges that have resulted from the government of Canada's decision to legalize MAID. 8,9,[18][19][20] Our broader study also discovered that participants encountered many challenges, ethical dilemmas, and moral distress in navigating MAID. 6 Shaw et al 10 reported physicians' rewarding experiences providing MAID in British Columbia.…”
Section: Discussionmentioning
confidence: 80%